2017
DOI: 10.1002/dneu.22497
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of matrix metalloproteinase triggers transdifferentiation of retinal pigmented epithelial cells inXenopus laevis: A Link between inflammatory response and regeneration

Abstract: In adult Xenopus eyes, when the whole retina is removed, retinal pigmented epithelial (RPE) cells become activated to be retinal stem cells and regenerate the whole retina. In the present study, using a tissue culture model, it was examined whether upregulation of matrix metalloproteinases (Mmps) triggers retinal regeneration. Soon after retinal removal, Xmmp9 and Xmmp18 were strongly upregulated in the tissues of the RPE and the choroid. In the culture, Mmp expression in the RPE cells corresponded with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…Remarkably, ECM is a privileged TH target. TH significantly regulates a large number of ECM components and remodelling enzymes during Xenopus metamorphosis (22,23,49). Moreover, TH-induced modulations of ECM components and proteases have also been reported in mammalian hearts (50,51).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Remarkably, ECM is a privileged TH target. TH significantly regulates a large number of ECM components and remodelling enzymes during Xenopus metamorphosis (22,23,49). Moreover, TH-induced modulations of ECM components and proteases have also been reported in mammalian hearts (50,51).…”
Section: Discussionmentioning
confidence: 96%
“…5H). Altered expression of matrix metalloproteinases that strongly influence ECM remodelling (22,23,49) may explain the profound change in connective tissue deposition and dynamics observed following cardiac amputation in treated animals (Figs. 4 and 5 and SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histologic examination has revealed that pigment granules are phagocytosed by both corneal epithelial cells and trabecular meshwork cells rather than being adsorbed onto their surface [ 11 14 ]. Phagocytic stress causes alterations to the trabecular meshwork extracellular matrix structure and adhesion [ 15 , 16 ] which could explain the trabecular meshwork dysfunction observed in PDS/PG patients [ 14 ]. In PDS/PG patients, trabecular meshwork cells die and exhibit localized necrosis [ 17 ].…”
Section: Pathophysiologymentioning
confidence: 99%